Validitas Perancangan Game Edukasi Berbasis Android pada Mata Pelajaran Informatika - Menrisal; Popi Radyuli; Liling Nurul Mukziza (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to describe the validity of Android-based educational game learning media in the Informatics subject at SMK Negeri 9 Padang. This research is a Research and Development study conducted in class X at SMK Negeri 9 Padang. The test subjects in this study were class X students majoring in Culinary and Hospitality. The instrument used is a media validation sheet which will be validated by material experts, media experts and linguists. The results of the assessment of the three validators obtained a validity test of 88.81%, so that the validity level can be interpreted as very valid to use. In conclusion, based on the assessment along with expert input as well as the results of field trials of Android-based educational games, the feasibility, excellence, and can be used in the learning process in Informatics class X SMK N 9 Padang